Photochemistry of S-phenacyl xanthates - Veetil, Aneesh Tazhe; Solomek, Tomáš; Ngoy, Bokolombe Pitchou; Pavlíková, Nela; Heger, Dominik; Klán, Petr (The Journal of organic chemistry, 2011)
Various synthetically readily accessible S-phenacyl xanthates are shown to undergo photoinitiated homolytic scission of the C-S bond in the primary step. The resultant fragments, phenacyl and xanthic acid radicals, recombine to form symmetrical 1,4-diketones and xanthogen disulfides, respectively, in high to moderate chemical yields in chemically inert solvents. They can also be efficiently trapped by a hydrogen-atom-donating solvent to give acetophenone and xanthic acid derivatives. The latter compound is in situ thermally converted to the corresponding alcohol in high chemical yields. S-Phenacyl xanthates could thus be utilized as synthetic precursors to the above-mentioned compounds or as photoremovable protecting groups for alcohols in which the xanthate moiety represents a photolabile linker. The photochemically released phenacyl radical fragments efficiently but reversibly add to the thiocarbonyl group of the parent xanthate molecule. The kinetics of this degenerative reversible addition-fragmentation transfer (RAFT)/macromolecular design via the interchange of xanthates (MADIX) mechanism was studied using laser flash photolysis (LFP) and density functional theory (DFT) calculations. The rate constants of the RAFT addition step, k(add) ∼ 7 × 10(8) M(-1) s(-1), and phenacyl radical addition to a double bond of 1,1-diphenylethylene, k(add) ∼ 10(8) M(-1) s(-1), in acetonitrile were experimentally determined by LFP. In addition, photoinitiation of the methyl methacrylate polymerization by S-phenacyl xanthate is demonstrated. The polydispersity index of the resulting poly(methyl methacrylate) was found to be ∼1.4. We conclude that S-phenacyl xanthates can serve simultaneously as photoinitiators as well as RAFT/MADIX agents in polymerization reactions.